Beneficiaries of Rehabilitation - Bickenbach, Jerome (Arch Phys Med Rehabil, 2021)
Recent research and the actions of the World Health Organization (WHO) have clarified the nature and value of rehabilitation as a key health strategy of the 21st century. However, strengthening rehabilitation in national health systems around the world is a challenge, partly because there is not an evidence-based argument that rehabilitation is a good economic and social investment. This argument, in turn, depends on characterizing the current and potential beneficiaries of rehabilitation, namely the individuals who could benefit from rehabilitation services whether or not they currently receive these services. Although identifying current beneficiaries is essential for evaluating the current demand for rehabilitation in existing health systems, as well as for making the economic investment case for rehabilitation within national health systems, it is only by characterizing potential beneficiaries that we can identify unmet needs and the potential social effect of rehabilitation. The objective of this study is to take a preliminary step toward both tasks by offering an overview of intuitively plausible approaches to characterizing beneficiaries of rehabilitation and to highlight limitations and challenges with each approach. We rely on the WHO's definition of rehabilitation, particularly the aim of rehabilitation to "optimize functioning and reduce disability," as our starting point.